ANALYSIS OF MEDIUM FUND SOURCES FOR MEDIUM BUSINESS GROWTH IN THE FINANCIAL SECTOR - Lie Lie; Muhammad Fajar Erdiawan; Marlina; Indrayani; Damsar; Muammar Khaddafi (PT. Radja Intercontinental Publishing, 2023)
This study aims to analyze the various sources of funds available to medium-sized businesses in the financial sector. The sources of funds analyzed include banks and financial institutions, venture capital, capital markets, cooperatives and government programs. The research method used is survey and analysis of secondary data obtained from verified sources. The survey was conducted on 100 respondents who are owners or managers of medium-sized businesses in the financial sector. Data analysis was performed using descriptive techniques and inferential statistics. The results show that banks and financial institutions are the most common source of funds used by medium-sized businesses in the financial sector, followed by venture capital and capital markets. Cooperatives are also a significant source of funding, especially for small and medium enterprises. In addition, government programs also make an important contribution in providing medium-sized funds through financial assistance, subsidies, and low interest loans. In conclusion, choosing the right source of funds is very important for the growth and development of medium-sized businesses in the financial sector. Understanding the advantages and limitations of each source of funds can help medium-sized entrepreneurs make wise decisions in accessing the funds they need. This research is expected to provide useful insights for entrepreneurs, financial institutions and the government in supporting the growth of the financial sector and medium enterprises as a whole